Islamic banking - Abdul Aziz, Hassanuddeen (IIUM Press, 2009)
Islamic Banking is designed to provide an introduction to Islamic banking and finance for students at universities and similar tertiary institutions. This book is also a source of general understanding ofthe concept of Islamic banking and finance and it will be beneficent not only for students but also for the laymen. I believe that the approach to Islamic banking and finance taken in this book will provide a solid foundation towards understanding the concept of Islamic finance. An effort has been made to provide an overview of the principles of Islamic commercial law in business and Islamic financial dealings. This book has been written with the objective of conveying an understanding of Islamic banking and finance, without introducing unnecessary technical terminology and procedures. It was written to develop a clear understanding ofthe prohibition of Riba, the instruments or products offered by Islamic banks, the contemporary approaches and practices across banks worldwide, and the challenges and future prospects ofIslamic banking. As in the conventional banking system, the Islamic banking system also has its sources of funds and various forms of applying these funds in order to generate reasonable profits and maximize its shareholders' wealth. Students will be able to appreciate and acknowledge the inbenmt equity of Islamic principles towards commercial and financial transactions. eedIess to say, it our responsibility to educate and enlighten the younger generation about the veracity and authenticity of Islamic ideologies and the undeniable fact that Islam is a complete way of life. The establishment of the institution of Islamic Banking and Finance and its continual successful growth during the last four decades had proved beyond doubt that Muslims around the can successfully develop a sound financial system without relying on the Wester financial system. However, the challenges and problems that the Islamic banking system are facing are discussed in this book to help the students appreciate the inherent complications associated economics in every business environment.